Arabic Language Debates to Enhance Speaking Competence at Islamic Boarding Schools - Rodiatul Maghfiroh; Bakri Muhammad Bakheet; Mohammad Shohibul Anwar (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study aims to describe the characteristics, supporting factors, inhibitory factors and its implications in improving students' speaking competence at the Al Amien Prenduan Islamic Boarding. The research is conducted using a qualitative approach through data collection methods that include interviews, observations, and discussion groups. The study subjects consist of active students who participate in debate activities and mentors or related teachers. Data were analyzed using NVivo software to perform coding and thematic analysis, which allows for the identification of main themes and sub-themes related to the implementation of the debate program. The research results show that the characteristics of the debate program include the use of Standard Arabic, the active role of mentors, and the structuring of ethically stimulating debate discussions. Supporting factors include teacher support, adequate facilities, and motivation from fellow students. On the other hand, inhibitory factors encompass limitations in preparation time, disturbances from the surrounding environment, and obstacles related to the complexity of the language. The analysis using NVivo reinforces the findings that active student involvement in debate not only enhances speaking skills but also strengthens confidence and ethical conduct during discussions. The implications of this program include the enhancement of communication, effective oral communication skills, and the formation of character-responsive students who engage in ethical speaking. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan karakteristik, faktor pendukung, faktor penghambat serta implikasinya dalam meningkatkan kompetensi berbicara siswa di Pondok Pesantren Al Amien Prenduan. Penelitian dilakukan dengan menggunakan pendekatan kualitatif melalui metode pengumpulan data yang meliputi wawancara, observasi, dan kelompok diskusi. Subjek studi terdiri dari siswa aktif yang mengikuti kegiatan debat dan mentor atau guru terkait. Data dianalisis menggunakan perangkat lunak NVivo untuk melakukan pengkodean dan analisis tematik, yang memungkinkan identifikasi tema utama dan sub-tema yang terkait dengan pelaksanaan program debat. Hasil penelitian menunjukkan bahwa karakteristik program debat meliputi penggunaan bahasa Arab Standar, peran aktif mentor, dan penataan diskusi debat yang merangsang secara etis. Faktor pendukung antara lain dukungan guru, fasilitas yang memadai, dan motivasi dari sesama siswa. Di sisi lain, faktor penghambatan mencakup keterbatasan waktu persiapan, gangguan dari lingkungan sekitar, dan hambatan yang terkait dengan kompleksitas bahasa. Analisis menggunakan NVivo memperkuat temuan bahwa keterlibatan aktif siswa dalam debat tidak hanya meningkatkan keterampilan berbicara tetapi juga memperkuat kepercayaan diri dan perilaku etis selama diskusi. Implikasi dari program ini meliputi peningkatan komunikasi, keterampilan komunikasi lisan yang efektif, dan pembentukan siswa yang responsif karakter yang terlibat dalam berbicara etis.